2020
DOI: 10.1038/s41467-019-14226-7
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-dependent control of a plasmodesmal regulator creates a negative feedback loop modulating lateral root emergence

Abstract: Lateral roots originate from initial cells deep within the main root and must emerge through several overlying layers. Lateral root emergence requires the outgrowth of the new primordium (LRP) to coincide with the timely separation of overlying root cells, a developmental program coordinated by the hormone auxin. Here, we report that in Arabidopsis thaliana roots, auxin controls the spatiotemporal expression of the plasmodesmal regulator PDLP5 in cells overlying LRP, creating a negative feedback loop. PDLP5, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
(45 reference statements)
1
57
0
Order By: Relevance
“…Higher auxin levels might therefore be present in those cells in the mutant. Considering the positive role of auxin in altering cell wall components to facilitate passage of the new root across the tissues of the primary one (reviewed in Péret et al, 2009), this well agrees with the observed increased lateral root emergence in the mutant (Sager et al, 2020).…”
Section: Reciprocal Feedbacks Between Auxin and Plasmodesmata Auxin Msupporting
confidence: 81%
See 2 more Smart Citations
“…Higher auxin levels might therefore be present in those cells in the mutant. Considering the positive role of auxin in altering cell wall components to facilitate passage of the new root across the tissues of the primary one (reviewed in Péret et al, 2009), this well agrees with the observed increased lateral root emergence in the mutant (Sager et al, 2020).…”
Section: Reciprocal Feedbacks Between Auxin and Plasmodesmata Auxin Msupporting
confidence: 81%
“…It was shown that ectopic induction of PDCB1 resulted in reduced emergence, likely because of callose induction in tissues overlying LRPs (Maule et al, 2013). This was confirmed in Sager et al (2020) by overexpressing another protein, PD localised protein (PDLP) 5. When the native domain of expression of PDLP5 was studied, the authors observed that signal occurred in cell layers above LRPs and accompanied lateral root emergence.…”
Section: Reciprocal Feedbacks Between Auxin and Plasmodesmata Auxin Mmentioning
confidence: 88%
See 1 more Smart Citation
“…Callose-dependent changes of the PD aperture are responsible for the directional diffusion of auxin in midrib and petiole epidermis cells [ 49 ], and higher PD permeability for auxin was seen in gsl8 mutants, compared to wild-type plants [ 50 ]. Callose synthesis was also found to be indispensable during the formation of the apical-basal axis and the development of the embryonic root [ 45 , 46 , 51 , 52 ].…”
Section: Do Callose-dependent Changes Of Pd Permeability Regulate Transient Auxin Gradients?mentioning
confidence: 99%
“…Lipid characterization of isolated plasmodesmata revealed that they are significantly enriched in sterols and sphingolipids containing α-hydroxylated VLCFAs and phytosphinganine (tri-hydroxylated long chain base t18:0) (Grison et al, 2015;Liu et al, 2020). Phytosphinganine binds plasmodesmata-located protein 5 (PDLP5) which regulates plasmodesmata cell-to-cell connectivity (Liu et al, 2020;Sager et al, 2020). Furthermore, the sphingolipid biosynthesis phloem unloading modulator (plm) mutant has reduced level of VLCFA-ceramides and displays enhanced cell-to-cell trafficking between the pericycle and the endodermis (Yan et al, 2019).…”
Section: Vlcfas Are Regulating Cell-to-cell Transport During Defined mentioning
confidence: 99%